Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.57187/smw.2017.14398
|View full text |Cite
|
Sign up to set email alerts
|

The conservative and pharmacological management of chronic subdural haematoma: a systematic review

Abstract: Chronic subdural haematoma (cSDH), one of the most common neurosurgical entities, occurs typically in elderly patients. The incidence is expected to double by the year 2030, owing to the continuous aging of the population. Surgery is usually the treatment of choice, but conservative treatment may be a good alternative in some situations. We provide a systematic review of studies analysing the conservative treatment options and the natural history of cSDH. Of 231 articles screened, 35 were included in this syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 50 publications
(74 reference statements)
3
20
0
Order By: Relevance
“…Our conclusion is consistent with that of a recent meta-analysis of 6 studies comprising 756 patients with CSDH, which also suggested that ATO could improve prognosis and neurological recovery (He et al, 2021). Additionally, some studies even suggest that ATO is as effective as surgery in patients with mild CSDH (Shofty and Grossman, 2016;Soleman et al, 2017). Currently, low-dose ATO has been used by many neurosurgeons to promote CSDH absorption and prevent the recurrence of CSDH (Wang et al, 2014;Chan et al, 2017;Tang et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Our conclusion is consistent with that of a recent meta-analysis of 6 studies comprising 756 patients with CSDH, which also suggested that ATO could improve prognosis and neurological recovery (He et al, 2021). Additionally, some studies even suggest that ATO is as effective as surgery in patients with mild CSDH (Shofty and Grossman, 2016;Soleman et al, 2017). Currently, low-dose ATO has been used by many neurosurgeons to promote CSDH absorption and prevent the recurrence of CSDH (Wang et al, 2014;Chan et al, 2017;Tang et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The findings in the cases suggest BHC is the most widely used and most accepted treatment option in symptomatic CSDH, which is in line with up-to-date literature (Kolias et al, 2014;Soleman et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Chronic subdural hematoma (CSDH) is a common neurosurgical disease, and the increase is shown as the population aging nowadays. Studies have predicted that CSDH will become the most common brain disease among adults by 2030 (1,2). When individuals with CSDH develop evident clinical symptoms, conservative therapy is relatively ineffective and surgery is often the only option (3).…”
Section: Introductionmentioning
confidence: 99%